To solve this problem you must apply the proccedure shown below:
1. You have the following expression given in the problem above:
[tex] \frac{1}{(x+2)}+\frac{1}{5}=\frac{6}{(x+5)} [/tex]
2. You need to find the least common denominator on the rigth member of the equation and then, you must sum both fractions:
[tex] \frac{(2)(5)+(x+2)}{5(x+2)} =\frac{6}{(x+5)}\\\frac{(x+12)}{(5x+10)}=\frac{6}{(x+5)} [/tex]
3. Now, solve for [tex] x [/tex], as following:
[tex] (x+12)(x+5)=6(5x+10)\\ x^{2} -13x=0 [/tex]
4. Factor out the [tex] x [/tex]:
[tex] x(x-13)=0\\ x=0; x=13 [/tex]
The answer is: [tex] x=0\\ x=13 [/tex]